Influence of Cultivation Conditions on the Nutritional Composition and Bioactive Components of two Undervalued Edible Plants (Porophyllum Ruderale and Portulaca Oleracea) (Global Journal of Science Frontier Research, 2022)
Wild plants have received considerable attention regarding ethnobotanical and pharmacological aspects. However, the potential of wild edible plants in terms of their nutritional and bioactive benefits has been investigated in only a few cases, despite being an important food source. This study aims to be a reference to promote the inclusion of two undervalued food plants as a nutritional alternative for balanced and healthy diets. The nutritional composition and bioactive components of Poriphyllum ruderale and Portulaca oleracea, two Mediterranean species, have been evaluated under wild and organic farming conditions. The quantification of nutrients and bioactive compounds was carried out with leaves and small stems of fresh plants. The proximal and mineral composition was determined with the official methods. The analysis of antioxidants was carried out with the DPPH technique and of total phenolic compounds by Folin-Ciocalteu. Other chemical components such as nitrates, pH and total acidity were determined.
Keywords: undervalued species; nutritional composition; bioactive compounds; P ruderale; Poleracea